The Legal Nature of Artificial Intelligence: An Analytical Study in Libyan Civil Law - Al-haj Hasan, Afaf Abdallah; Gashoot, Ahmad Ramadan (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study aims to shed light on the nature of artificial intelligence (AI) and to highlight the subtle differences between AI and human intelligence. It further seeks to clarify the appropriate legal classification of AI actions and behaviors in order to determine the applicable rules of liability for errors resulting from its operation. To address these complex issues, the study adopts a descriptive and analytical approach within the framework of Libyan civil law. The research led to several findings, the most significant of which is the necessity of enacting specific legislation to regulate the liability of artificial intelligence. Such legislation should be based on the concept of functional capacity, which differs fundamentally from the legal capacity attributed to natural persons.